Reading Enhancement tool - Jibreen, Nour; Al-Jebrini, Mohammed (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2010)
Huge amount of information is issued every moment. Most of those who want to be always up-to-date with what come out of books, articles and reports do not have enough time to read all this amount of information. In addition to that , many of those have slow reading speed. By reading faster , we can increase the amount of information we get. Our application guarantees fast reading but making sure to get the information not just skimming or scanning what we are reading. We implemented a windows application that is built to measure the speed reading, comprehension rate and enhancement of reading for slow readers, we have employed experimented methods for improving reading speed and measuring comprehension rates, based on practical research that was implemented by speed Arabic expert.
no of pages 93, 25300, هندسة حاسوب 1/2010 , in the store
Keywords: Reading Enhancement tools